(untitled) (American Journal of Islam and Society, 1994)
The Islamization of knowledge, as envisioned by al Faruqi, is a critical, revivalistic response to intellectual modernity.’ Its objective is a timeless but it can only be realized by challenging it and engaging Muslim scholars in debate over it. By so doing, we are able to refine the work plan for Islamization. The following critique is therefore presented in the hope that its suggestions will contribute toward an authentic Islamic tespotlse to intellectual modernity. Exposition of Islamization For al Faruqi (1982), the some of the crisis of Muslim society lies in the mdem-Islamic dichotomy of the current educational system. The colonial, and therefore alien, vision still survives and is being disseminated through educational institutions, which are the breeding ground of self-estrangement from Islam. Such early educational reformem as Sayyid Ahmad Khan and Muhammad ’Abduh did not realize the harm of modem knowledge, for they assumed that modem subjects are harmless and can only lend sttength to the Muslims. Little did they realize that the alien humanities, social sciences, and indeed the natural sciences as well, wee facets of an integral view of reality, of life and the world, of history, that is equally alien to that of Islam. (Ibid.) One of his particular concerns is the harmful influence of a university education on a Muslim student whose sentimental attachment to Islam cannot withstand the onslaught of scientific truth. After four years of alienating influence, his/her Islamic consciousness would be ravaged. The solution to this alienation is to be found in the Islamization of knowledge, an understanding that seeks to rebuild the humanities, as well as the social and natural sciences, in order to establish them fitmly on an Islamic basis consistent with Islamic objectives. Every discipline is to be "recast" to embody the principles of Islam and remolded to incorporate the "relevance" of Islam along a triple axis constitutive of tawhid (unity) ...